Pathogenetic therapeutic tactics in case of true gynecomastia - V. A. Ivanov; I. A. Ozerskaya; D. V. Akimov (ABV-press, 2014)
The characteristics of the treatment tactics of the non-nodular forms of gynecomastia as mammary gland's cancer prevention is given in the ar- ticle on the basis of the own observations and the example of the work of domestic and foreign authors. Variants of the mono- and combined drug therapy are analyzed. Treatment results are given. An attempt was made to determine the priority of the treatment variants being used.